KEBERHASILGUNAAN PENYULUHAN BAHASA INDONESIA DI KALIMANTAN TENGAH - Budhiono, Ralph Hery (SUAR BETANG, 2017)
Penyuluhan Bahasa Indonesia is an annual educational event conducted by Balai Bahasa Kalimantan Tengah. Elementary school teachers all over Kalimantan Tengah usually be the main target since they hardly learn the Indonesian language academically and specifically. Socializing the national language of Indonesia, spreadingnewest issues of the language and improving speakers ability are the main idea. Language and speakers cultivation is its major aim. The effectivity of such event has not been evaluated yet. Based on this fact the writer wants to figure out the effectivity of Penyuluhan Bahasa Indonesia. The problems discussed in this writing will be how are the participants’ scores of pre-test and post-test. This scores then analyzed to identify whether Penyuluhan Bahasa Indonesia is truly effective. sample of this writing are 71 elementary schools teachers from two regions, namely Pangkalan Bun and Kuala Kapuas. The data are then analyzed statistically. Based on the findings, the average scores of those two sessions test were not satisfied yet. Meanwhile, the event of Penyuluhan Bahasa Indonesia influences the scores significantly and improves teachers ability. In general, based on scores, Pangkalan Bun as a more dynamic region considered to be more superior in average score than Kuala Kapuas.